Effect of autovaccine on bacterial infection in mice - Ning Rintiswati, Ning Rintiswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: In the present time therapy with antibiotics does not always solve the problem of infectious disease. Many factors influence infectious disease including immun mechanism, disease, resistant strain of microorganism, etc. Immunotherapy using autovaccine could be an alternative therapy, especially on chronic ulcer.Objective:The study observed the effect of autovaccine on ulcer of mice infected by various single bacteria and mix of bacteria.Methods :One hundred and eighty female mice were divided into 3 groups, group 1 was infected by Stapylococcus aureus, group 2 by E.coli, group 3 by mix bacteria (P. aeruginosa, Stapylococcus aureus, E. cob), and ten mice served as control. Half of each group of infected mice then was given autovaccine subcutaneously once a day for seven days. Development of skin lession was observed daily until recovery occured. Titer antibody against bacterial was evaluated using agglutination test.Results: Autovaccine group recovered faster than untreatment group. Number of death in infected group was higher than control group. Autovaccine increase antibody titer in mix bacterial infected group, and group infected by S.aureus, but had no effect on antibody production on group infected by E.coli. Conclusion: Autovaccine has no effect on recovery of skin lession of single infected mice, but effective to heal in mix infected mice.Key words: autovaccine - immunostimulator - bacterial infection - antibody - ulcer healing